2018
DOI: 10.3389/fchem.2018.00043
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Implementation of the Nwat-MMGBSA Method to Rescore Docking Results in Medium-Throughput Virtual Screenings

Abstract: Nwat-MMGBSA is a variant of MM-PB/GBSA based on the inclusion of a number of explicit water molecules that are the closest to the ligand in each frame of a molecular dynamics trajectory. This method demonstrated improved correlations between calculated and experimental binding energies in both protein-protein interactions and ligand-receptor complexes, in comparison to the standard MM-GBSA. A protocol optimization, aimed to maximize efficacy and efficiency, is discussed here considering penicillopepsin, HIV1-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 110 publications
(167 reference statements)
1
64
0
Order By: Relevance
“…In addition, we applied a solid VS procedure we recently developed and which was shown to be successful in discriminating active from inactive compounds within the screening of classical small molecules and protein–protein interaction inhibitors. 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we applied a solid VS procedure we recently developed and which was shown to be successful in discriminating active from inactive compounds within the screening of classical small molecules and protein–protein interaction inhibitors. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Results of Nwat-MMGBSA rescoring, using 30 explicit waters, are the only reported, since Nwat=30 was considered a reasonable value in previous publications. [12,15] As it can be observed, the protease inhibitor Indinavir, [16] currently used to treat HIV infections, has been selected by both targets. Additionally, the other protease inhibitors Lopinavir [17] and Atazanavir [18] are also top ranked for 3CL-PRO.…”
Section: Resultsmentioning
confidence: 99%
“…The Virtual Screening (VS) was done accordingly to our recently developed protocol. [12] The protocol is applied using a set of scripts (available for download as Supplementary Material within ref. [12]) that do the following steps automatically: 1.…”
Section: Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the top docking ranked poses are the lowest ranked poses using MM/GBSA rescoring, that indicates the rescoring of few top poses, if binding could not be determined through docking programs or binding is nonspecific. In many studies it has been well demonstrated that MM/GBSA approach is most accurate and reliable for ranking (“scoring”) the efficacy/affinities of a ligand binding to the receptor proteins in the protein–ligand docked complexes ( Singh and Warshel, 2010 ; Sun et al, 2014 ; Wright et al, 2014 ; Genheden and Ryde, 2015 ; Maffucci et al, 2018 ). MD simulations analysis therefore, could be employed for accurate ranking of ligands following the post docking program in terms of their binding affinities ( Okimoto et al, 2009 ; Chen, 2015 ).…”
Section: Discussionmentioning
confidence: 99%